Parenting Culture of Low-Income Families in Implications for the Subjective Well-being of Early Childhood Students - Sri Wahyuni; Azlin Atika Putri; Reswita Reswita (STAI Hubbulwathan Duri, 2021)
Poverty has a negative impact on parenting patterns that can reduce the subjective well-being) of childhood. This study aims to reveal the parenting skill of low-income families to improve the subjective well-being of childhood. This type of descriptive research with 119 parents in Pekanbaru comes from low-income families who live in Pekanbaru. Results of the study revealed parenting skills respondents (41%) require information about good parenting to develop the potential of children for the child's positive development, the child's goodness, and independence. While 22% want their children to be successful and have a better future, they do not use the correct method, and 18% of respondents want their children to be more normative, more obedient, have good habits, and be accepted by society. About 14% of respondents want their children to achieve better academic performance, and 5% want their children to be happy and happy later. The conclusion is Parenting skills of low-income families in improving subjective well-being of early childhood is not optimal.